Robotic Therapy: Cost, Accuracy, and Times. New Challenges in the Neonatal Intensive Care Unit - Amodeo, Ilaria; Pesenti, Nicola; Raffaeli, Genny; Sorrentino, Gabriele; Zorz, Alessia; Traina, Silvia; Magnani, Silvia; Russo, Maria Teresa; Muscolo, Salvatore; Plevani, Laura; Mosca, Fabio; Cavallaro, Giacomo (Frontiers in Pharmacology, 2019)
Background: The medication process in the Neonatal Intensive Care Unit (NICU), can be challenging in terms of costs, time, and the risk of errors. Newborns, especially if born preterm, are more vulnerable to medication errors than adults. Recently, robotic medication compounding has reportedly improved the safety and efficiency of the therapeutic process. In this study, we analyze the advantages of using the I.V. Station® system in our NICU, compared to the manual preparation of injectable drugs in terms of accuracy, cost, and time. Methods: An in vitro experimental controlled study was conducted to analyze 10 injectable powdered or liquid drugs. Accuracy was calculated within a 5% difference of the bottle weight during different stages of preparation (reconstitution, dilution, and final product). The overall cost of manual and automated preparations were calculated and compared. Descriptive statistics for each step of the process are presented as mean ± standard deviation or median (range). Results: The median error observed during reconstitution, dilution, and final therapy of the drugs prepared by the I.V. Station® ranged within ±5% accuracy, with narrower ranges of error compared to those prepared manually. With increasing preparations, the I.V. Station® consumed less materials, reduced costs, decreased preparation time, and optimized the medication process, unlike the manual method. In the 10 drugs analyzed, the time saved from using the I.V. Station® ranged from 16 s for acyclovir to 2 h 57 min for teicoplanin, and cost savings varied from 8% for ampicillin to 66% for teicoplanin. These advantages are also capable of continually improving as the total amount of final product increases. Conclusions: The I.V. Station® improved the therapeutic process in our NICU. The benefits included increased precision in drug preparation, improved safety, lowered cost, and saved time. These advantages are particularly important in areas such as the NICU, where the I.V. Station® could improve the delivery of the high complexity of care and a large amount of intravenous therapy typically required. In addition, these benefits may lead to the reduction in medication errors and improve patient and family care; however, additional studies will be required to confirm this hypothesis.